Analisis Sistem Pendaftaran Merek dalam Kasus Pembatalan Merek Zhe Nung Zhu (Studi Putusan Mahkamah Agung Nomor 704K/Pdt.Sus-HKI/2021) - Yolanda Pusvita Sari; Saidin; Hasim Purba (CV Rewang Rencang, 2025)
Indonesia applies the First to File trademark registration system based on Law No. 20 of 2016 on Trademarks and Geographical Indications which provides legal protection to the party who first registers their trademark, however its implementation faces challenges such as in the case of cancellation of the trademark